The Devastating Economic Impact of COVID-19 on Older Black and Latinx Adults: Implications for Health and Well-Being. (30th November 2021) - Garcia, Marc A; Thierry, Amy D; Pendergrast, Claire B
Abstract: Objectives: While disparities in coronavirus disease 2019 (COVID-19) infections and mortality have been documented for older Black and Latinx populations, pandemic-related economic impacts have been less studied for these groups. Minoritized older adults may be particularly vulnerable to financial hardships given their precarious socioeconomic positions. Thus, we aim to highlight the devastating economic impact of the ongoing COVID-19 pandemic and subsequent economic recession on older Black and Latinx adults, with a particular focus on the foreign-born population. Methods: This study used data from the 2020 COVID-19 module of the Health and Retirement Study. The sample included adults older than 50 years of age who were U.S.-born non-Latinx White and Black, U.S.-born Latinx, and foreign-born Latinx ( n = 2, 803). We estimated age-standardized prevalence and means of variables indicating financial impact and economic hardship during the pandemic. We further examined differences in these measures across racial/ethnic and nativity groups. Results: Our findings document stark racial/ethnic inequalities in the pandemic's economic impact on older adults. Results show the pandemic has negatively affected older Black and Latinx adults across a host of economic factors (e.g., paying bills, affording health-related needs, or purchasing food), with foreign-born Latinx experiencing greater economic hardships relative to other groups. Discussion: During the COVID-19 pandemic, older Black and Latinx adults are experiencing disparate economic effects, including lacking money to cover basic needs, compared to older White adults. The implications of the economic shocks of the pandemic for the health and well-being of older Black and Latinx adults warrant policy-oriented action toward promoting equity.